PENGARUH BEBAN KERJA, STRES KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PJLP UNIT PENGELOLA RUMAH SUSUN IV - Putri Penta Utari; Lia Amalia (Jurnal Pijar, 2023)
One of the organizational resources that has an important role in achieving its goals is human resources. This study aims to determine the effect of workload, work stress and job satisfaction on employee performance at PJLP UPRS IV simultaneously and partially. This study aims to determine the effect of workload, work stress and job satisfaction on employee performance oat PJLP oUPRS oIV osimultaneously oand opartially. oTo oknowing owhich ovariables oof oworkload, owork stress and ojob osatisfaction omost odominantly oaffect oemployee operformance oat oPJLP oUPRS oIV. oThis ostudy ouses oa onon-probability osampling oapproach owith oa osaturated osampling otechnique. oThe opopulation oin othis ostudy owere oall oemployees owith oa ototal oof o161 orespondents. oData owere ocollected ousing oa oquestionnaire owith oonline odistribution oto oemployees. oThen the data is oprocessed oby omultiple olinear oregression omethod. oThe odata oanalysis owere ocarried oout owith othe ohelp oof othe oSPSS otool. Based on the results of the analysis, it is known that the variables of workload, work stress, and job satisfaction have a simultaneous effect on employee performance. Partially, the workload and job satisfaction variables have a positive effect on employee performance. While the work stress variable has a negative effect on employee performance . Then the results of the analysis, the most dominant variable ffecting employee performance is othe job satisfaction variable.